Phenotypic Heterogeneity in Resistance and Biofilm Formation Among Clinical Acinetobacter baumannii Isolates in Northwestern Mexico - Alma Karen Orozco-Ochoa; Jean Pierre González-Gómez; José Benigno Valdez-Torres; Nohelia Castro-del Campo; Cristóbal Chaidez-Quiroz (Journal of Genome Biotechnology and Genetics, 2026)
Acinetobacter baumannii is a major nosocomial pathogen characterized by multidrug resistance and persistence in hospital environments. This study evaluated antimicrobial susceptibility and biofilm-forming capacity in ten clinical A. baumannii isolates obtained from a tertiary care hospital in Northwestern Mexico to explore phenotypic traits associated with persistence. Minimum inhibitory and bactericidal concentrations were determined using broth microdilution according to Clinical and Laboratory Standards Institute guidelines. All isolates were resistant to ciprofloxacin, whereas variable resistance was observed for tobramycin (60%) and ceftazidime (20%); all strains remained susceptible to colistin. Bactericidal assays revealed heterogeneous responses across antibiotics. Biofilm formation, assessed by crystal violet staining, showed that most isolates produced weak to moderate biofilms, while three strains were non-producers. Significant variability in biofilm biomass was observed (p < 0.001). Notably, no direct association was found between antimicrobial resistance profiles and biofilm-forming capacity, indicating phenotypic heterogeneity among isolates. These findings suggest that persistence-related traits in A. baumannii may not be solely predicted by resistance patterns, highlighting the complexity of adaptive responses under antimicrobial stress.